IDENTIFIKASI SISTEM AGROFORESRTI (TUMPANGSARI) DALAM PERTANIAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA DI DUSUN SREMBEN, KABUPATEN MAGELANG - Ahsan Risfathoni Almadani; Wahyu Gilang Hermawan (Yayasan Nusantara Hasana Berdikari, 2023)
Agroforestry or intercropping is a land use and management system by combining forest plants with agricultural crops or livestock with the aim of obtaining optimal and efficient results. Sremben Hamlet is one of the hamlets in Wulunggunung Village, Sawangan District, Magelang Regency which utilizes land as agricultural land. This study aims to determine the agroforestry system in agriculture and its contribution to the household income of the Sremben hamlet community. The method used in this study is the observation method in the Sremben Hamlet area regarding the land that uses the agroforestry system and the types of plants on that land. Land measurement is carried out to calculate the average area of ​​land used. As for the total income data of farmers from agroforestry land, it was collected through interviews using the snow balling method. The results showed that there were 5 agricultural lands using the agroforestry system (intercropping) in Sremben Hamlet, Wulunggunung Village, Sawangan District, Magelang Regency. The agroforestry system contributes to the income of farmer households on only planted seasonal crops. For annual plant species, it is utilized from an ecological perspective and as a potential for future savings for personal needs. As for the grass that is deliberately planted on the land is used as animal feed that they have.